Study on the Capture Effect of Particle Trap in 1000 kV AC GIL - Jinggang Yang; Ke Zhao; Tianxin Zhuang; Hongtao Li; Yun Teng; Jianjun Liu; Zhiyue Sang (IEEE Access, 2023)
In this paper, a 1000 kV gas insulated transmission line (GIL) prototype with a basin insulator and a three-post insulator structure was designed and developed to study the particle motion behavior in an ultra high voltage (UHV) GIL. Particle traps were arranged on the convex side of the basin insulator and near the three-post insulator. Aluminum and copper particles were arranged in front of and on the surface of the traps. A short-time voltage application procedure and a graded long-time voltage application procedure were designed to investigate the difference in the capture effect of the traps on the two types of particles when the test voltage was applied to the prototype through these two voltage application procedures. The results of the study show that the particle motion behavior is complex under AC voltage. The placement of the particles, their own properties and the voltage application procedure all affect the motion behavior of the particles. The trap with the grid structure is effective in capturing particles near both the convex side of the basin insulator and the three-post insulator. At the end of the test, some of the particles went inside the trap and some of them gathered at the edge of the trap. The graded long-time voltage application procedure with a small voltage application gradient and a long duration enables the particles to move sufficiently at a lower voltage to be trapped.